Grid connection approach for very small-scale pico-hydro systems using PV microinverters - Ribeiro, Gabriela Moreira (2020)
The use of renewable energy sources has grown significantly in recent decades, with emphasis on resources that have a low environmental impact in the energy production process. Small-scale pico-hydro systems have great potential and are also in line with increasing environmental requirements.